MEAN SQUARE ERROR TERKECIL DARI KOMBINASI PENAKSIR RASIO-PRODUK UNTUK RATA-RATA POPULASI PADA SAMPLING ACAK BERSTRATA - Rini Kurniati; Sigit Sugiarto; Rustam Efendi (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This paper discussed about three the ratio-product estimators for mean population in thestratified random sampling. It is combinations of ratio estimator and product estimatorin stratified random sampling. This paper is a review from the paper of Tailor et.al.[Communications of the Korean Statistical Society 18:111-118]. The estimatorsdiscussed are the combination of ratio-product estimator, combination of ratio-productestimator using coefficient of variation and combination of ratio-product estimator usingcoefficient of kurtosis. All of estimators are bias estimator. Then the mean square error(MSE) of each estimator is evaluated. Furthermore, the MSE of each estimator iscompared. This comparison shows that the combination of ratio-product estimator is themost efficient, that is with the smallest MSE.